Is innovation needed in the Old World wine market? The perception of Italian stakeholders. Issue 6 (11th June 2018) - Wongprawmas, Rungsaran; Spadoni, Roberta
Abstract : Purpose: The wine market in Italy has been through several changes in the last decade. Actors in the supply chain need to find new strategies or tools in order to remain competitive in what has become a fiercely competitive sector. Innovation is one of the tools which have been successfully used in the New World wine market, hence innovation might also be a useful resource for actors in the Old World wine market, such as in Italy. The purpose of this paper is to explore stakeholders' perception of such innovation, including how its usefulness in the Italian wine production and distribution chain is perceived. Design/methodology/approach: Semi-structured interviews were carried out in Emilia-Romagna with a wide range of actors in the Italian wine chain and consumer focus groups and the resulting data were analyzed using the content-summarizing approach. Findings: These stakeholders agreed that innovation is needed for production and processing as well as in quality control, but only on condition that it should maintain the quality and value of traditional wines. Innovative wine products tend to be unacceptable to consumers. Most stakeholders associate innovation with communication as producers and distributors seek innovative ways to convey information regarding the value of wines to final consumers. Research limitations/implications: The findings are qualitative and based on a small group of Italian wine industry players and consumers who operate mainly in a domestic context. Practical implications: The paper provides industrialists with information useful in the search to find the right strategies to make them more competitive in the Italian wine market. It is crucial to find and adopt innovative approaches toward communication throughout the chain. Information appealing to tradition and sentiment could be highly effective ways to reach the consumer. Originality/value: This is the first in-depth study of the perceptions of all stakeholders (from producers to consumers) regarding innovation in the Italian wine chain; of particular importance as the industry is currently in transition toward globalization.